Change and continuity management in the public sector : the DALI model for effective decision-making - Dalli Gonzi, Rebecca (Emerald Publishing Limited, 2019)
The customer problem in the public sector appears when too many processes are in place and staff volumes are too large to adapt to sudden change. As situations evolve and solutions are required, public managers are faced with an overload of information for decision-making, as normal day-to-day policy is overlooked to accommodate management by crisis. Generally, emergency situations call for effective steps to be taken, constrained by short time frames and a dispersed public workforce.Managing teams require structure in their response to an evolving crises, which is generally a difficult position to attain when information and resources are limited. Protocol and response plans are only activated in extreme crises, leaving a gap in response when overload has been reached but is not within the stipulated margins. Recognition at this stage is important if successful outcomes are to be achieved. This book proposes an 8-point model, which it labels the DALI Model, for responding to these situations, to simplify and synthesize decision-making processes.
Keywords: Organizational behavior -- Management.; Decision making.; Business & Economics -- Decision-Making & Problem Solving.; Business & management.; elektronické knihy; electronic books